Comparison of the efficacy of the Epley maneuver and repeated Dix–Hallpike tests for eliminating positional nystagmus: A multicenter randomized study - Imai, Takao; Uno, Atsuhiko; Yamato, Akiyuki; Takimoto, Yasumitsu; Sato, Go; Matsuda, Kazunori; Takeda, Noriaki; Nishiike, Suetaka; Kawashima, Kayoko; Iga, Tomoko; Ueno, Yuya; Ohta, Yumi; et al. (Frontiers in Neurology, 2023)
Background and Objectives Patients with benign paroxysmal positional vertigo of the posterior canal (pc-BPPV) exhibit BPPV fatigue, where the positional nystagmus diminishes with repeated performance of the Dix-Hallpike test (DHt). BPPV fatigue is thought to be caused by the disintegration of lumps of otoconial debris into smaller parts, and can eliminate positional nystagmus within a few minutes (similar to the immediate effect of the Epley maneuver; EM). In this study, we aimed to show the non-inferiority of the repeated DHt to the EM for eliminating positional nystagmus after 1 week. Methods This multicenter, randomized controlled clinical trial was designed based on the CONSORT 2010 guidelines. Patients who had pc-BPPV were recruited and randomly allocated to Group A or Group B. Patients in Group A were treated using the EM and patients in Group B were treated using repeated DHt. For both groups, head movements were repeated until the positional nystagmus had been eliminated (maximum of three repetitions). After 1 week, the patients were examined to determine whether the positional nystagmus was still present. The groups were compared in terms of the percentage of patients whose positional nystagmus had been eliminated, with the non-inferiority margin set at 15%. Results Data for a total of 180 patients were analyzed (90 patients per group). Positional nystagmus had been eliminated in 50.0% of the patients in Group A compared with 47.8% in Group B. The upper limit of the 95% confidence interval for the difference was 14.5%, which was lower than the non-inferiority margin. Discussion This study showed the non-inferiority of repeated DHt to the EM for eliminating positional nystagmus after 1 week in pc-BPPV patients, and that even the disintegration of otoconial debris alone has a therapeutic effect for pc-BPPV. Disintegrated otoconial debris disappears from the posterior canal because it can be dissolved in the endolymph or returned to the vestibule via activities of daily living. Classification of Evidence This study provides Class II evidence of the non-inferiority of repeated DHt to the EM for eliminating positional nystagmus after 1 week. Registration Number: UMIN000016421